Terapi Wicara Dan Auditori Verbal Terhadap Perkembangan Bahasa Pada Anak Tunarungu - Mutia Mawardah; Ajeng Kusumawardany (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2023)
Development is the changes that occur in a person’s life span, where this development begins during pregnancy. However, in some cases these developments do not go as they should. One of the things that happens is that the hearing function does not develop properly which canresult in the inhibition of a person’s communication development. The subjects of this studywere deaf children who were attending speech and auditory verbal therapy at PT. ABDI Palembang. The number of samples in this study were five deaf children who use hearing aidsor cochlear implants. This sampling technique is purposive sampling technique is the sample is determined based on certain criteria.The result of this study in dicate that the reisan influence between speech therapy and auditory verbal on language development in deaf children at PT.ABDI Palembang which was shown through the paired sample t-test with p=0.003 so thatp<0.05 and the distribution value through the Kolmogorov-Smirnov test with p=0.2 so thatp>0.01. One of the changes that occurred in the sample after receiving speech therapy and auditory verbal therapy was starting to understand their own name, this was seen when the sample turned around when his name was called 2 to 3 times by giving a waiting time